Pengaruh Kinerja Room Service Waiter Terhadap Kualitas Pelayanan Di Hotel Best Western Premier Solo Baru - Hanung Wijayanto; Budi Purnomo; Kris Cahyani Ermawati (Sekolah Tinggi Pariwisata Sahid Surakarta, 2019)
The performance of the room service waiter in the room service section is something that must always be considered to maintain the quality of service which is basically a standard than the Best Western Premier Solo Baru Hotel. This research uses descriptive qualitative which describes the problem by searching, collecting, recording, selecting and analyzing based on relevant theory, using observation, interview, documentation, and literature study methods. In this study, it is explained that the efficiency/smoothness of work and guest satisfaction can be obtained through the excellent work speed of each room service staff in delivering food, accuracy in ordering food according to demand and timeliness of delivery as well as the responsibilities of each room service staff in make the atmosphere in the room service section comfortable and make work smooth. The results of this study can be concluded that the performance of the room service waiter has been good, as evidenced by the lack of guest complaints and good online guest comments from guests. From the information above, it can be concluded that with the speed, accuracy, and good responsibility of each room service staff, it will lead to good efficiency/smooth work and will make guests feel satisfied with the services provided by the room service section